Pain in Thalassemia: The Effects of Age on Pain Frequency and Severity - Haines, Dru (1984)
Pain is not a symptom generally associated with thalassaemia. However, providers have noted increasing patient reports of pain, creating an impetus for this prospective, observational assessment of pain in thalassaemia patients. The primary study goals were to assess pain prevalence, severity, location, and potential risk factors. This was a multicentre, prospective study of thalassaemia patients receiving care at 12 Thalassaemia Clinical Research Network (TCRN) sites. Pain was assessed using the Brief Pain Inventory (BPI). 252 thalassaemia patients ranging in age from 12 to 71 years (mean 28.8) were enrolled. Sixty-four percent reported experiencing pain during the last four weeks, 22% of whom reported pain on a daily basis. Ordinal regression analysis of pain ratings demonstrated significant (P < 0.001) correlation of increased age with increased pain, irrespective of diagnosis, transfusion status, gender, bone density, chelator type or iron overload. Eighty-one percent reported having pain for one year or longer and 31% reported pain for five or more years. Pain is a major cause of morbidity and an unrecognized problem for patients with thalassaemia. Age is the strongest predictor of frequency and severity. Little else is known about the aetiology and predictors of this pain syndrome.